Best Buy: collective wisdom in decision making - Birkinshaw, Julian (Henry Stewart Talks, 2018)
This case study examines Best Buy and the business’s use of collective or crowd wisdom. One senior executive had his employees estimate the likely sales of greetings cards that would be sold during the upcoming holiday season and this estimate proved to be significantly more accurate than that of the experts who traditionally estimated these numbers.